PENDAMPINGAN KELOMPOK UMKM UNTUK MENGHASILKAN PRODUK UNGGULAN DAERAH DAN PERIJINAN USAHA DI KECAMATAN JOGOROGO KABUPATEN NGAWI JAWA TIMUR - Maretha berlianantiya; Ninik Srijani; Kevin Prasetya; Aprilia Syafitri; Ervi Aulia Rahma (Fakultas Ekonomi Universitas Surakarta, 2024)
The aim of the Community Service Team activities carried out in Jogorogo Village, Jogorogo District, Ngawi Regency is to explore the village's potential so that it can be used as a regional superior product and assist MSMEs who do not yet have business permits with Online Single Submission. Participants in this activity were representatives of the Jogorogo village government and MSME groups. Methods used: Preparation stage, assessment and agreement stage, action planning and activity implementation stage, action planning and activity implementation stage, evaluation stage, termination stage. The results of this service activity were the first to discover the village's potential, namely the abundance of rambutan fruit which was successfully made into processed rambutan fruit as a superior product for the Jogorogo region. Secondly, 12 MSMEs have successfully registered with the OSS for business licensing.